Stereotypy of a Spatial Operant in Pigeons and the Law of Effect - Hiller, George (My University, 1987)
The consequences of food reinforcement in pigeons were studied on a circular response continuum in which 72 possible keypeck responses were equated for effort. When every keypeck was rewarded equally, the pigeons did not come to peck in any particular location in the response continuum, contrary to expectations from the Law of Effect. Instead, they spread their keypecks over the entire continuum. Likewise, when a randomly-selected 20% of their keypecks were reinforced, the pigeons did not progressively concentrate their keypecks in any particular location. Successful shaping of keypecking to 12 evenly-spaced target locations shows that the pigeons could discriminate between different locations, and that they could be shaped to respond to each of the locations equally well. When it was discovered that each pigeon was making shifts between keys from trial to trial which were consistent in direction and magnitude, these shifts were also examined for progressive stereotypy. None was found in their behavior either. Successful shaping of particular size and direction of shifts showed that this behavior could be controlled by reinforcement, although not precisely as location of pecking. Analysis of shifts following reinforced and non-reinforced trials in the random-reinforcement and location shaping conditions revealed a tendency for the pigeons to make consistent small shifts following reinforced trials, and more diffuse and much larger shifts following non-reinforced trials. Small consistent shifts were also generally found when every trial was reinforced, and large diffuse shifts when no trials were reinforced. These findings were discussed in relation to reinforcement theory, and also to optimal foraging theory.